Implementation of Data-Driven Planning in Supporting Learning Quality - Rizki Fauzan; Harjito; Nurkolis; Prasetyo Listiaji (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study explores the data-driven planning cycle to improve learning quality at a public senior high school in Pemalang Regency, Indonesia. Using a qualitative case study design, data were collected from six informants (the principal, vice-principals, and teachers) through interviews, observations, and document analysis. The findings reveal that the school systematically executes four integrated stages, starting with identifying problems using the Education Report Card, followed by collaborative reflection to determine root causes, proceeding to the formulation of improvement plans focused on literacy strengthening and differentiated instruction, and concluding with the adaptive implementation and evaluation of programs in the classroom. This study concludes that this mechanism transcends administrative compliance, serving as a continuous improvement engine essential for enhancing the accuracy of pedagogical decision-making. These findings imply that this structured cycle can serve as a practical framework for other educational institutions to translate school data into targeted learning improvements effectively.